PENGARUH FAKTOR-FAKTOR SISTEM PENILAIAN KINERJA TERHADAP KOMITMEN KERJA KOPERASI KARYAWAN REDRYING BOJONEGORO (KAREB) KABUPATEN BOJONEGORO - jurnalpps pps; Diana Trisnawati; Mei Indrawati; Hidayat ÔÇÄ (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
The purpose of this study is to describe a performance appraisal system consisting of work attitudes, work performance, work intelligence and work commitment. Furthermore, to analyze the influence both simultaneously and partially on the performance appraisal system consisting of work attitudes, work performance, work intelligence simultaneously has a significant effect on work commitment in the Redrying Bojonegoro (Kareb) Employee Cooperative in Bojonegoro Regency. This type of research is explanatory research, namely research that aims to test hypotheses using a quantitative research approach. The population in this study were all employees of the Redrying Bojonegoro Employee Cooperative (Kareb) in Bojonegoro Regency, DC Unit, which numbered 31 people. The research sampling technique used saturated sampling (census sampling) so that the sample in this study were 31 people. The results showed that partially or simultaneously the variables of work attitude and work intelligence had a significant effect on employee commitment, while the work performance variable did not significantly affect the commitment of employees of the Bojonegoro (Kareb) Employee Cooperative in Bojonegoro Regency. Among the factors of work attitude, work performance and work intelligence that have a dominant influence on employee commitment are work attitudes.